Tomato yellow leaf curl virus differentially influences plant defence responses to a vector and a non‐vector herbivore. (5th January 2016) - Su, Qi; Mescher, Mark C.; Wang, Shaoli; Chen, Gong; Xie, Wen; Wu, Qingjun; Wang, Wenkai; Zhang, Youjun
Abstract: Plants frequently engage in simultaneous interactions with diverse classes of biotic antagonists. Differential induction of plant defence pathways by these antagonists, and interactions between pathways, can have important ecological implications; however, these effects are currently not well understood. We explored how Tomato yellow leaf curl virus (TYLCV) influenced the performance of its vector ( Bemisia tabaci ) and a non‐vector herbivore ( Tetranychus urticae ) occurring separately or together on tomato plants ( Solanum lycopersicum ). TYLCV enhanced the performance of B . tabaci, although this effect was statistically significant only in the absence of T . urticae, which adversely affected B . tabaci performance regardless of infection status. In contrast, the performance of T . urticae was enhanced (only) by the combined presence of TYLCV and B . tabaci . Analyses of phytohormone levels and defence gene expression in wild‐type tomatoes and various plant‐defence mutants indicate that the enhancement of herbivore performance (for each species) entails the disruption of downstream defences in the jasmonic acid (JA) pathway. For T . urticae, this disruption appears to involve antagonistic effects of salicylic acid (SA), which is cumulatively induced to high levels by B . tabaci and TYLCV. In contrast, TYLCV was found to suppress JA‐mediated responses to B . tabaci via mechanisms independent of SA. Abstract : Plants in both natural and agricultural ecosystems frequently engage in complex interactions with diverse classes of biotic antagonists. We explored how Tomato yellow leaf curl virus (TYLCV) influenced the performance of its vector ( Bemisia tabaci ) and a non‐vector herbivore ( Tetranychus urticae ) occurring separately or together on tomato plants ( Solanum lycopersicum ). We found that the combined presence of TYLCV and B . tabaci significantly enhanced the performance of T . urticae, an effect likely mediated by anatagonistic crosstalk between the jasmonic‐acid (JA)‐mediated and salicylic‐acid (SA)‐mediated defence pathways. In contrast, we found that TYLCV suppressed JA‐mediated responses to B . tabaci via mechanisms independent of SA, although this effect was only statistically significant in the absence of T . urticae, whose presence adversely affected B . tabaci performance regardless of infection status.